Inventory Model for Perishable Products with Time Dependent Production and Demand under Shortage Conditions - Kumara Mohan Babu,; Dr.K.Aruna Kumari,; Anusha Karredla,,; Dr.Ponduri SB,; Dr.Puligilla .Prashanth Kumar, (Utilitas Mathematica, 2025)
This study develops an enhanced economic production quantity (EPQ) model for decaying items, incorporating time-dependent production and demand rates while allowing for shortages. The model assumes that items lifetime follow an exponential distribution. A comprehensive total cost function is formulated, accounting for relevant cost components. By minimizing this function, optimal production schedules and quantities are determined. Additionally, there is an increase in costs and key parameters.